The Concept of Kafa'ah in Modern Society from Islamic Legal Perspective - Wahab, Abdul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The concept of kafa'ah is an important aspect of marriage in society to determine the suitability of a couple. The actulization of kafa'ah can vary between communities which is influenced by local values ​​and developing traditions. This article examines the concept of kafa'ah from the perspective of Islamic family law and the actualization of the concept of contemporary marriage kafa'ah. This paper uses a literature review as a data source. It was found that the concept of kafa'ah in the sociological context of modern Islamic society refers to the principle of harmony or suitability between partners in various aspects of life. This term is often used in the context of marriage, where the compatibility between prospective husband and wife is assessed in various aspects, such as social, economic, cultural, and religious backgrounds. A marriage that is considered kafa'ah is a marriage between two people who have similar religious beliefs or at least have a high level of conformity in religious practices; have a good level of conformity in terms of social norms and community values; conformity with customs, traditions and cultural values ​​believed in by the community; suitability of educational level.